ANALISIS PENGARUH PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN ROTI AGUNG MARTAPURA - Norrahmiati; Safitri, Dwi Wulan (Scientific : Jurnal Ilmu-Ilmu Sosial dan Ekonomi, 2021)
Promotional activities not only function as a communication tool between companies and consumers, but also as a tool to influence consumers in purchasing activities or using products according to their needs and desires. Indonesia has a variety of food. One of them is a business in the culinary field which is currently very promising. UMKM Roti Agung is a business in the culinary field located in the city of Martapura, South Kalimantan. The purpose of this study is to analyze the effect of promotion on consumer purchasing decisions for Roti Agung Martapura. The study was conducted at the Roti Agung MSME located on Jalan Taruna Praja No 2 Rt 11 Sungai Sipai Village, Martapura. The data collection techniques in this study used questionnaires or questionnaires, documents, observations and interviews. The questionnaire given is in the form of a set of closed or open written questions to respondents to answer. The variable of this study uses the independent variable, namely promotion (X), while the dependent variable is purchase decision (Y). The results of this study reveal 1) The results of the partial test or t test show the effect of the variable X (promotion) on the consumer decisions of Roti Agung Martapura with a tcount value of 8.781 and a t-table value of 1.992 so that we can see that tcount > ttable, it is stated that Ho rejected and Ha accepted where the promotion variable had a partial effect on consumer purchasing decisions for Roti Agung Martapura, and 2) R square value of 0.507, which means that the percentage of promotion variables can explain the variable purchasing decisions of consumers of Roti Agung Martapura of 50.7 % while the remaining 49.3% is explained by other variables outside of this study.